Comparative Evaluation of Enzymatic Crude Protein Degradation in Selected Legume Forages - Hanoğlu Oral, Hülya (My University, 2024)
For protein evaluation of feedstuffs for ruminants, the Streptomyces griseus protease test offers a purely enzymatic approach to estimate ruminal protein degradation. This study was conducted to determine the enzymatic crude protein (CP) degradability of alfalfa, sainfoin, and common vetch hays, which are commonly used in ruminant nutrition. To estimate CP degradation, fifteen samples from each type of hay were incubated in vitro with a commercial protease extracted from Streptomyces griseus. The incubation was carried out for 1, 4, 24, and 48 hours in a borate- phosphate buffer at pH 8. Significant differences in CP degradability values were found among all three types of hay across all incubation periods. For all incubation periods, sainfoin had the lowest CP degradability values (P < 0.05), due to its high content of cell wall components and condensed tannins (CTs). For incubation periods longer than 1 hour, common vetch had the highest CP degradability values, followed by alfalfa and sainfoin, respectively (P < 0.05). As a result, the use of the protease enzyme extracted from Streptomyces griseus was confirmed as an effective method for estimating the CP degradability of selected legume forages in the laboratory, eliminating the need for animal testing. However, since plant proteins are often embedded within carbohydrate complexes, it is recommended that future tests consider the combined use of protease and carbohydrase, particularly for sainfoin, which is rich in cell wall components and condensed tannins.
Keywords: Alfalfa, Sainfoin, Common vetch, Streptomyces griseus protease, Protein degradation